Hubungan Manajemen Waktu dan Dukungan Sosial Teman Sebaya Dengan Prokrastinasi Akademik Pada Siswa Kelas XII SMAN 4 Bekasi - Mediastuti, Rahma; Nurhadianti, Rr Dini Diah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2021)
The purpose of this study was to see the relationship between time management and peer social support with academic procrastination of student of class XII in SMAN 4 Bekasi. The subjects of this study was the student of class XII in SMAN 4 Bekasi, with a population of 358 students. The sampling technique used is the convenience sampling. This research is a quantitative study that uses 3 measuring instruments, namely: academic procrastination scale, time management scale, and peer social support scale. The results showed that there was a significant and negative relationship between time management and academic procrastination with r -0.762 and p = 0.000 < 0.05. There was a significant and negative relationship between peer social support and academic procrastination with r -0.354 and p = 0.000 < 0.05. There was a significant relationship between time management and peer social support with academic procrastination of student of class XII in SMAN 4 Bekasi with R = 0.767 and p = 0.000 < 0.05.